Invisible water in subducted crust: Lawsonite velocity anomalies under mantle conditions - Sibo Chen; Siheng Wang; Xintong Qi; Man Xu; Tony Yu; Yanbin Wang; Baosheng Li (Proceedings of the National Academy of Sciences, 2025)
Subduction zones transport significant amounts of water into Earth’s mantle, primarily through hydrous minerals such as lawsonite. However, the seismic detectability of lawsonite-bearing oceanic crust at mantle depths remains uncertain. To address this issue, we measured sound velocities of lawsonite up to 7.4 GPa and 600 °C. Both P- and S-wave velocities exhibited unexpected increases with temperature under high-pressure conditions. Our result suggest that hydrous oceanic crust exhibits higher seismic velocities than the surrounding mantle at depths of 150 to 250 km, resulting in high-velocity anomalies rather than the previously assumed low-velocity anomalies. Furthermore, the seismic velocity difference between hydrous and dry oceanic crust is less than 2%, making it challenging to distinguish between them using seismic velocities. This limitation may hinder the detection of the hydration state in subducted crust. In addition, lawsonite remains stable in 90% of subduction zones, and thus, such “seismically invisible water” may exist in most subducted slabs around the world.